2022
DOI: 10.3389/fcell.2022.935318
|View full text |Cite
|
Sign up to set email alerts
|

WNK1 in Malignant Behaviors: A Potential Target for Cancer?

Abstract: Metastasis is the major cause of mortality in cancer patients. Analyses of mouse models and patient data have implicated the protein kinase WNK1 as one of a handful of genes uniquely linked to a subset of invasive cancers. WNK1 signaling pathways are widely implicated in the regulation of ion co-transporters and in controlling cell responses to osmotic stress. In this review we will discuss its actions in tumor malignancy in human cancers and present evidence for its function in invasion, migration, angiogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 139 publications
1
4
0
Order By: Relevance
“…Furthermore, we observed a dose-dependent increase in SYVN1 expression and a corresponding decrease in MNK1/2 and p-eIF4E levels upon treatment with increasing concentrations of VNLG-152R ( Figures 3C, D ). As expected, we also observed a dose-dependent decrease in other downstream oncoproteins involved in breast cancer cell migration, invasion, and cell cycle progression such as WNK1 (kinase with no lysine (K) 1) ( 45 , 46 ), and Cyclin-D1 ( 47 , 48 ), respectively ( Figure 3D ).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, we observed a dose-dependent increase in SYVN1 expression and a corresponding decrease in MNK1/2 and p-eIF4E levels upon treatment with increasing concentrations of VNLG-152R ( Figures 3C, D ). As expected, we also observed a dose-dependent decrease in other downstream oncoproteins involved in breast cancer cell migration, invasion, and cell cycle progression such as WNK1 (kinase with no lysine (K) 1) ( 45 , 46 ), and Cyclin-D1 ( 47 , 48 ), respectively ( Figure 3D ).…”
Section: Resultssupporting
confidence: 83%
“…Another significant finding of this study is that VNLG-152R caused dose-dependent depletion of WNK1 ( Figure 3D ) which is implicated in cell migration, invasion, and metastasis in multiple cancer types including glioblastoma ( 83 ), prostate cancer ( 84 ), non-small cell lung cancer ( 85 ), and breast cancer ( 45 , 46 , 86 , 87 ). Because metastasis is the major cause of mortality in patients with breast cancer ( 88 ), we posit that our compounds can be developed as small molecules therapeutics with the characteristics of inhibiting both cell proliferation and metastasis, which would undoubtedly have a major impact on mortality in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 62%
“…Importantly, recent studies revealed that TRIM27 is elevated in human cancers ( 59 ) and is required for TNBC tumor growth in mouse xenograft models ( 60 ). WNK1 also has been linked to multiple cancers ( 61 ). Our previous work demonstrated that WNK1 regulates endothelial cell migration and angiogenesis by regulating downstream signaling proteins ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that WNT1 tend to interact with hydrophobic domains of partner proteins "defending" them from abnormal aggregation [127]. WNK1 activity is known to correlate with tumor malignancy [128], but there is currently no evidence that pathologic WNK1 aggregation is associated with the disease.…”
Section: In Depth Analysis Of Highly Disordered Proteins From Various...mentioning
confidence: 99%